Static compression optical coherence elastography to measure the mechanical properties of soft contact lenses - Quince, Zachery (Biomed Opt Express, 2021)
In this study, a novel method was developed for estimating the elastic modulus (Young’s modulus) of soft contact lens materials using static compression optical coherence elastography. Using a commercially available spectral domain optical coherence tomography instrument, an experimental setup was developed to image a soft contact lens sample before and during compression with a known applied force, from which the lens material’s mechanical properties can be derived. A semi-automatic segmentation method using graph-search theory and dynamic processing was used to trace the lens boundaries and to determine key structural changes within the images. To validate the method, five soft contact lens materials with a range of known elastic moduli and water contents were tested. The proposed method was successful in estimating the Young’s modulus in the five different soft contact lens materials. It was demonstrated that the method provides highly repeatable measurements, with an intraclass correlation coefficient of >95%. The Young’s modulus results were compared to published manufacturer data with no significant difference for four out of the five materials (p > 0.05). These results demonstrate that a static compression optical coherence tomography method can reliably measure the elastic modulus of soft contact lenses. This provides a methodology that can be used to explore in vitro contact lens mechanical properties, but more importantly, may also be extended to study the mechanical characteristics of in vivo or ex vivo tissue, provided that they can be imaged using OCT.